State border fences as a threat to habitat connectivity a case study from South-Eastern Europe = Ograde na državnim granicama kao prijetnja povezanosti staništa : studija slučaja iz Jugoistočne Europe - Safner, Toni; Gracanin, Ana; Gligora, Ivan, agronom; Pokorny, Boštjan; Flajšman, Katarina; Apollonio, Marco; Šprem, Nikica (2021)
The conservation value of transboundary management of wildlife populations in Europe, that marked end of the 20th and the beginning of the 21th century, has come under huge pressure since 2015 especially in the South-eastern Europe due to border fences construction in response to large influxes of refugees/migrants. The primary aim of this study was to present data on the direct impacts of the long fence on wildlife (e.g. fence-related mortality) across the Hungary–Croatia border. We collected data on fence-related animal mortality along 136 km of the fence in the first 28 months after its construction. In total, 64 ungulates (38 red deer, 23 roe deer, and three wild boar) were found entangled in or deceased due to the razor wire fence. In addition, we present direct (photographic) evidence of newly recorded behaviour of red deer, as they gather in huge herds attempting to cross the border fence between Hungary and Croatia. Short term effect of the border fence is reflected in direct animal mortality, and as obstruction to the movement and behaviour of animals. In the case that current fences will remain or continue to expand along the northern boundary of South-eastern Europe, it is likely that fragmented wildlife populations in the region will suffer from negative effects of genetic subdivision such as loss of alleles and reduced heterozygosity that can cause important long-term damage to their vitality.
Konzervatorska vrijednost prekograničnog gospodarenja populacijama divljih životinja u Europi, koja je obilježila kraj 20. i početak 21. stoljeća, našla se pod velikim pritiskom od 2015., posebice u jugoistočnoj Europi, zbog izgradnje graničnih ograda kao odgovor na velike prilive izbjeglica/migranata. Primarni je cilj ovoga rada predstaviti podatke o izravnim utjecajima ograde na divlje životinje (npr. smrtnost od ograde) preko mađarsko–hrvatske granice. Prikupili smo podatke o smrtnosti životinja vezanih uz granične ograde (ukupne dužine 136 km) u prvih 28 mjeseca poslije konstrukcije. Ukupno je pronađeno 64 dvopapkara (38 jelena običnog, 23 srne obične i tri divlje svinje) upleteno ili uginulo zbog bodljikave žice. Uz to, predstavljamo izravne (fotografske) dokaze o novo zabilježenom ponašanju jelenske divljači, okupljajući se u velika krda koja pokušavaju prijeći graničnu ogradu između Mađarske i Hrvatske. Kratkoročni učinak granične ograde ogleda se u obliku izravne smrtnosti životinja, a isto tako i kao opstrukcije kretanju i ponašanja životinja. Ako postojeće ograde ostanu ili se nastave širiti duž sjeverne granice jugoistočne Europe, vjerojatno je da će fragmentirane populacije divljih životinja u regiji patiti od negativnih učinaka genetske podjele, poput gubitka alela i smanjene heterozigotnosti, što može izazvati dugoročno značajnije štete u vitalnosti tih populacija.
Bibliografija: str. 275-276.
Summary ; Sažetak.
Keywords: Divljač -- Granice -- Granične ograde -- Stradanja divljači; Jugoistočna Europa